PHÂN TÍCH XÁC ĐỊNH NỒNG ĐỘ DIOXIN/FURAN VÀ DL-PCB TRONG THỨC ĂN CHĂN NUÔI BẰNG HỆ THỐNG SẮC KÝ KHÍ KHỐI PHỔ BA TỨ CỰC - Nguyễn, Thị Thu Lý; Trần, Đình Phiên; Nguyễn, Thị Thu; Nguyễn, Đức Thắng (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
DETERMINATION OF DIOXIN/FURAN AND DL-PCB IN ANIMAL FEED USING GAS CHROMATOGRAPHY TRIPLE QUADRUPOLE MASS SPECTROMETRY (GC-MS/MS) This study presents a method for ultra-trace analysis of polychlorinated dibenzo-p-dioxin/dibenzofuran (PCDD/Fs) and dioxin-like polychlorinated biphenyls (dl-PCBs) in animal feed using gas chromatography triple quadrupole mass spectrometry (GC-MS/MS). The GC-MS/MS system has a good capability to separate the isomers of PCDD/F and dl-CB, with the overlap level of TCDD isomers not exceeding 30%, meeting the analytical requirements of US EPA Method 1613B and 16130. The linear range of the calibration curve is 0.05-40 pg/µL for TCCD/F, 0.25-200 pg/µL for PeCDD/F-HpCDD/F, 0.5-400 pg/µL for OCDD/F, and 0.2-2000 pg/µL for dl-PCB. The method demonstrated detection limits of 0.005-0.076 pg/g for PCDD/Fs and 0.025-0.050 pg/g for dl-PCBs. Samples analysis revealed that the total toxic equivalency (TEQ) of PCDD/Fs and dl-PCBs in animal feed samples ranged from 0.197 to 0.418 pg TEQ/g, which is below the maximum allowable limits set by the European Commission for animal feed. These findings validate the applicability of GC-MS/MS as a reliable confirmatory tool for qualitifying PCDD/Fs and dl-PCBs in complex feed matrices.